Cladophialophora bantiana – A rare cause of soil-transmitted fungal brain abscess in tropical countries - Dipankar Pal; Adrian Keith Noronha; Rini Bandyopadhyay; Abi Manesh S (IDCases, 2023)
Cladophialophora and other dematiaceous or pigmented fungi are inhabitants of soil and decaying vegetation in tropical and sub-tropical environments. It usually causes subcutaneous phaeohyphomycosis post-inoculation by thorns or vegetable matter prick. It may be inhaled into paranasal sinuses and lungs with subsequent clearance by intact host immunity. In immunocompromised individuals, it can cause invasive sinusitis or pneumonitis followed by hematogenous dissemination to involve distant organs, particularly the brain. Disseminated disease with hematogenous brain abscess is found occasionally. We encountered such an interesting case and successfully treated it with surgical drainage followed by dual anti-fungal therapy.